1982
DOI: 10.1002/jlac.198219820511
|View full text |Cite
|
Sign up to set email alerts
|

Aromatensynthese aus 1,2,3‐Selenadiazolen und α‐Pyronen

Abstract: Anhand der Verbindungen 8a -f, h -j und l o g wird eine einfache Aromatensynthese beschrieben. Der wesentliche Schritt ist dabei die [x2 + ,4]-Cycloaddition von Cycloalkinen 3 an a-Pyrone 9, eine Diels-Alder-Reaktion mit inversem Elektronenbedarf. Als Cycloalkin-Vorstufe werden die entsprechenden 1,2,3-Selenadiazole 2 eingesetzt. Der GesamtprozeB 2 + 9 -t 8 wird ermoglicht durch die Eliminierung von N,, Se und CO, in dieser Reihenfolge. Synthesis of Aromatic Hydrocarbons from 1,2,3-Selenadiazoles and a-Pyrones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Therefore, we have chosen methyl coumalate (5), which is a commercially available electrophilic diene, as a possible reaction partner for enyne 4. [13] The inverse-electron-demand Diels-Alder reaction took place chemoselectively to afford 6. The modularity of the synthetic routine allows, at this point, the introduction of differently substituted fused aryl rings by utilising other dienes (e.g., 2H-pyran-2-ones or tetrazines) to access a variety of monoarylcyclooctynes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we have chosen methyl coumalate (5), which is a commercially available electrophilic diene, as a possible reaction partner for enyne 4. [13] The inverse-electron-demand Diels-Alder reaction took place chemoselectively to afford 6. The modularity of the synthetic routine allows, at this point, the introduction of differently substituted fused aryl rings by utilising other dienes (e.g., 2H-pyran-2-ones or tetrazines) to access a variety of monoarylcyclooctynes.…”
Section: Resultsmentioning
confidence: 99%
“…2 Such units have been found in various natural products as well as in pharmacologically active substances:3, 4 Iprindole ( 1 ),5 the first second‐generation antidepressant (TCA), and jolynamine ( 2 ),6 which was isolated from a dark brown alga belonging to the family Scytosiphonaceae, contain a cycloocta[ b ]indole skeleton (Figure 1). Very limited methods, especially those involving the unfavorable formation of eight‐membered rings, have been developed for the synthesis of these type of products 2b,c,d. 7 Thus, new methodologies for the efficient synthesis of this type of skeleton are highly desired.…”
Section: Methodsmentioning
confidence: 99%
“…13 C spectra were referenced to residual chloroform at δ 77.0 ppm and the signals are reported as chemical shift (ppm) followed by (in brackets) the peak assignment. Cyclooctyne was prepared according to Meier et al 12 and compounds 19, 20, 22, and 23 were previously reported. 5…”
Section: Methodsmentioning
confidence: 99%